Pengaruh J-Klik (Jujur, Korsa, Loyal, Inisiatif, Korektif) Terhadap Kinerja Pegawai di Lingkungan Kantor Wilayah Direktorat Jenderal Bea dan Cukai Sumatera Bagian Timur - Brata Rama Firdaus; Tien Yustini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of the research is to discover whether the Integrity, Esprit de Corps, Loyalty, Initiative, Corrective influence employee performance at Regional Office of the Directorate General of Customs and Excise for Eastern Sumatra. The type of the research is quantitative. Total population is 195 people from 4 work unit under subordinate of Regional Office of the Directorate General of Customs and Excise for Eastern Sumatra. The data analysis techniques used include descriptive statistical tests, instrument quality tests, classic assumption tests, multiple linear regression analysis, and hypothesis testing. The research findings indicate that integrity does not influence employee performance, while team spirit, loyalty, initiative, and corrective attitude do influence employee performance at the Regional Office of the Directorate General of Customs and Excise for Eastern Sumatra. Collectively, integrity, team spirit, loyalty, initiative, and corrective attitude influence employee performance at the Regional Office of the Directorate General of Customs and Excise for Eastern Sumatra